Dazzle 'em with style : the art of oral scientific presentation - Anholt, Robert Rene Henri, 1951- (Elsevier Academic Press, 2006)
Mastering the art of communicating scientific information is more critical than ever for a successful career in science and technology. Scientists today must be able to effectively convey sophisticated information to a broad audience that may include students, colleagues around the world, regulatory bodies, granting agencies, legislators, and the lay public. In this engaging and lively book, the author provides a step-by-step guide to the complete process of making a scientific presentation from preparation to delivery. It offers numerous examples highlighting what to follow and what to avoid. This revised edition covers the effective use of PowerPoint and other computer-based presentation programs. It also includes a handy checklist, new illustrations, and tips on handling an audience in a foreign country.